Orientation anisotropies in human primary visual cortex depend on contrast - Maloney, Ryan T.; Clifford, Colin W.G. (NeuroImage (Orlando, Fla.), 2015)
Orientation processing in visual cortex appears matched to the environment, such that larger neural populations are tuned to cardinal (horizontal/vertical) than oblique orientations. This may be manifested perceptually as a cardinal bias: poorer sensitivity to oblique compared to cardinal orientations (the “oblique effect”). However, a growing body of psychophysical data reveals the opposite pattern of anisotropy: a bias towards the oblique over the cardinal orientations (the “horizontal effect”), something matched by recent functional magnetic resonance imaging (fMRI) studies that have found an increased response to the oblique over the cardinal orientations in early visual cortex. This may reveal the operation of an efficient coding strategy optimised to the diet of orientations encountered during natural viewing. From consideration of coding efficiency, it might be expected that the anisotropies would change as the quality/strength of the oriented stimulus changes. In two experiments, fMRI response modulations were measured in retinotopically-defined human early visual cortex as a function of the contrast and orientation of sinusoidal gratings. Both experiments revealed a marked change in the V1 response from a cardinal (vertical) bias at low contrast to an oblique bias at high contrast. In Experiment 2, this was also apparent in areas V2 and V3. On average, there was no systematic “radial bias” (a preference for orientations aligned with the visual field meridian) in V1, although it was present in some individual subjects. The change in orientation anisotropies with contrast is consistent with an adaptive stimulus coding strategy in cortex that shifts according to the strength of the sensory inputs. •At low stimulus contrast, the V1 response was maximal for vertical orientations.•At high stimulus contrast, the V1 response was maximal for the oblique orientations.•Orientation coding may adaptively shift according to sensory signal-to-noise ratio.